Usulan Penerapan 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) pada Pembuatan Tas, Pouch, Dompet, dan Sabuk Kulit pada Erpat Leather, Yogyakarta - Emaputra, Andrean; Rusianto, Toto; Mawadati, Argaditia; Susetyo, Joko; Sodikin, Imam; Pohandry, Arie; Sekar Putu Waringin, Viajeng (Lembaga Pengembangan Kinerja Dosen, 2026)
Erpat Leather is a manufacturer of leather bags, pouches, wallets, and belts, located in Tirto RT 05, Bangunjiwo, Kasihan, Bantul, Yogyakarta. Some production materials are not arranged neatly, which can disrupt the smoothness of the production process. The business needs to improve the efficiency and smoothness of the production process. Then, community service activities were carried out by lecturers, educational staff, and students of the Industrial Engineering and Mechanical Engineering Study Programs of the University of AKPRIND Indonesia to increase the knowledge of Erpat Leather owners and workers about 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). Erpat Leather needed training to improve the smoothness of the production process, work efficiency, and work safety. This training began with a discussion between the service team and the business owner, followed by field observations by the service team, and continued with suggestions for improvement to the owner and workers, and ended with the delivery of conclusions and a group photo. The implementation of 5S at Erpat Leather is carried out through five stages, namely, first, sorting goods that are still in use and those that are no longer used; second, arranging goods in the production area in an orderly manner; third, cleaning the work environment regularly; fourth, maintaining the work area to keep it clean; fifth, disciplining good work habits, and providing slogans that cultivate 5S. This activity is expected to increase Erpat Leather's competitiveness in the leather product market by improving the smoothness of the production process.